A Comparative Study of Laminar-Turbulent Displacement in an Eccentric Annulus under Imposed Flow Rate and Imposed Pressure Drop Conditions - Yasaman Foolad; Majid Bizhani; Ian A. Frigaard (Energies, 2021)
This paper presents a series of experiments focused on the displacement of viscoplastic fluids by various Newtonian and non-Newtonian fluids from a long horizontal, eccentric annulus. The flow regimes range from high Reynolds number laminar regimes through to fully turbulent. These experiments represent the primary cementing operation in a horizontal well. The main objective of our experiments is to gain insight into the role of the flow regime in the fluid-fluid displacement flows of relevance to primary cementing. We study strongly eccentric annuli and displaced fluids with a significant yield stress, i.e., those scenarios where a mud channel is most likely to persist. For fully eccentric annuli, the displacements are uniformly poor, regardless of regime. This improves for an eccentricity of 0.7. However, at these large eccentricities that are typical of horizontal well cementing, the displacement is generally poor and involves a rapid “breakthrough” advance along the wide upper side of the annulus followed only by a much slower removal of the residual fluids. This dynamic renders contact time estimates meaningless. We conclude that some of the simple statements/preferences widely employed in industry do not necessarily apply for all design scenarios. Instead, a detailed study of the fluids involved and the specification of the operational constraints is needed to yield improved displacement quality.